Study on Quantitative Characterization of Morphological Characteristics and High Temperature Performance Evaluation of Coarse Aggregate Based on Computer Vision - Liu, Zhanliang; Zhang, Chen; Shao, Linlong; Wang, Jiangfeng (Frontiers in Materials, 2021)
The morphological characteristics of aggregate include outline shape, angularity and surface texture, which determine the mutual extrusion and friction between aggregates, and significantly affect the performance of asphalt pavement. At present, the research on the morphological characteristics of coarse aggregate is mainly focused on indoor visual identification technology (AIMS, XCT, etc.), which the applicability of the proposed aggregate shape characterization index is weak, and the aggregate testing equipment cannot effectively provide services for on-site construction control because of economy and portability. In this paper, the Coarse Aggregate Morphological Identification System (CAMIS) is developed based on computer vision technology, and the system can recognize the shape features of aggregates above 2.36mm particle size, and carry out uninterrupted feeding and removal based on the mechanical arm system, which can realize large sample detection. Based on CAMIS aggregate identification system and laboratory tests (rutting test, dynamic modulus test and penetration shear test), the shape identification and performance test of aggregate samples from construction site are carried out, and an aggregate performance evaluation index CEI suitable for high temperature area is proposed combination with the improved response surface method. The processing parameters of vertical shaft impact aggregate crusher are optimized based on CEI index, and the recommended processing parameters are verified by laboratory tests. The results show that the influence rank of morphological characteristics of coarse aggregate on its high temperature performance is angularity> needle flake> axial coefficient> convexity. The combination of processing parameters of vertical axis impact crusher is recommended of 45m/s rotational speed, 3t/h feed quantity and 30% air intake. Verified by laboratory tests, the aggregate identification system CAMIS developed in this paper and the proposed aggregate performance evaluation index CEI are highly reliable.